Ni mesh-reinforced ultrasonic-assisted Cu/Sn58Bi/Cu joint performance: Experiments and first-principles calculations - Xi Huang; Liang Zhang; Yu-hao Chen; Lei Sun; Xin-quan Yu; Quan-bin Lu (Ultrasonics Sonochemistry)
The Ni mesh was incorporated into the Cu/Sn58Bi/Cu bonding as a reinforcing skeleton to achieve an enhancement effect analogous to steel reinforcement in concrete. Ultrasonic-assisted soldering (UAS) improved the metallurgical bond among the solder, Ni mesh, and substrate. It facilitated the formation of (Cu, Ni)6Sn5 intermetallic compounds (IMCs) layers, increasing the joint strength. Observations indicated that ultrasonic treatment effectively refined the (Cu, Ni)6Sn5 grains and induced a uniform preferred orientation of β-Sn and Bi grains in the joint matrix adjacent to the Ni mesh. The shear strength of the joint reached 72.23 MPa when the ultrasonic application was sustained for 15 s, achieving the fabrication of a high-strength point with low energy consumption. First-principles calculations have confirmed that changes in the Ni content within (Cu, Ni)6Sn5 IMCs improved the stability of the crystal structure. Furthermore, the variations in content could potentially improve the mechanical and electrical properties of the (Cu, Ni)6Sn5. Enhancements in ultrasonic efficiency and the reinforcement of IMC structures offer new avenues for research in green and high-performance electronic packaging material joining technologies.